2017
DOI: 10.3847/1538-4357/aa5655
|View full text |Cite
|
Sign up to set email alerts
|

Consistent SPH Simulations of Protostellar Collapse and Fragmentation

Abstract: We study the consistency and convergence of smoothed particle hydrodynamics (SPH) as a function of the interpolation parameters, namely the number of particles N, the number of neighbors n, and the smoothing length h, using simulations of the collapse and fragmentation of protostellar rotating cores. The calculations are made using a modified version of the GADGET-2 code that employs an improved scheme for the artificial viscosity and power-law dependences of n and h on N, as was recently proposed by Zhu et al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
(135 reference statements)
1
15
0
Order By: Relevance
“…The location of the molecular bridge between the two disks ( Figure 6) is slightly east of the HST bifurcated bridge, but both seem to join the two disks of the system. The nature of this bridge is unknown, although it is well known from numerical simulations that multiple systems have bridges of material like the one observed here (e.g., Gabbasov et al 2017). We have also noticed that the optical bridge between the disks of the system has a curvature and joins the west side of SR24S with the east side of SR24N.…”
Section: Extended Gas Featuresmentioning
confidence: 54%
“…The location of the molecular bridge between the two disks ( Figure 6) is slightly east of the HST bifurcated bridge, but both seem to join the two disks of the system. The nature of this bridge is unknown, although it is well known from numerical simulations that multiple systems have bridges of material like the one observed here (e.g., Gabbasov et al 2017). We have also noticed that the optical bridge between the disks of the system has a curvature and joins the west side of SR24S with the east side of SR24N.…”
Section: Extended Gas Featuresmentioning
confidence: 54%
“…In order to describe the accretion process we must be able to obtain the radial velocity profile u(r) and the density ρ from Eqs. (7) and (9). Of course, depending on the nature of the matter content, the pressure can be obtained as a function of ρ from the equation of the state of the accreted matter.…”
Section: Relativistic Dust Accretionmentioning
confidence: 99%
“…For example, in contrast to most conventional kernels, Wendland functions do not allow particle motions on a sub-resolution scale (i.e., within the kernel support) and therefore they maintain quasi-ordered particle distributions even in highly dynamical test problems [56]. A Wendland function that has been adopted in many recent tests and simulations [13,30] is the Wendland C 4 kernel function given by W q, h 495 32πh 3 1 − q…”
Section: Consistency and Self-consistency Conditionsmentioning
confidence: 99%
“…A formal derivation of the error carried by the SPH interpolation by Sigalotti et al [29] has shown that the inconsistency is removed by increasing the number of neighbors. This was thereafter tested in the astrophysical context with reasonably good results [30,31]. In this approach no corrections to the SPH discretization are required and full particle consistency is restored in the asymptotic limit N → ∞, h → 0, and n neigh → ∞ with n neigh /N → 0, where N is the total number of particles, h is the smoothing length, and n neigh is the number of neighbors within the kernel support.…”
Section: Introductionmentioning
confidence: 99%